Law Enforcement Management and Administrative Statistics (LEMAS), 1993 ([Verlag nicht ermittelbar], 1996)
This survey, the third in the Bureau of Justice Statistics' program on Law Enforcement and Administrative Statistics (LEMAS), presents information on five types of general-purpose law enforcement agencies: state police, county police, special police (state and local), municipal police, and sheriff's departments. Variables include size of the population served by the police or sheriff's department, levels of employment and spending, various functions of the department, average salary levels for uniformed officers, policies and programs, and other matters related to management and personnel.